2002
DOI: 10.1021/np0105735
|View full text |Cite
|
Sign up to set email alerts
|

Two Unprecedented Dibromotyrosine-Derived Alkaloids from the Brazilian Endemic Marine Sponge Aplysina caissara

Abstract: Two new bromotyrosine-derived alkaloids, caissarine A (1) and caissarine B (2), along with three known biogenetically related alkaloids, aeroplysinin-1, fistularin-3, and the artifact of isolation 2-(3,5-dibromo-4-dimethoxy-1-hydroxy-2,5-cyclohexadien-1-yl)ethanamide, have been isolated from Aplysina caissara, an endemic species of marine sponge from the Southeastern Brazilian coast. The alkaloids have been identified by analysis of spectroscopic data. While caissarine A has a 2-hydroxyagmatine moiety in its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 25 publications
1
23
0
6
Order By: Relevance
“…Structurally related to aerothionin and homoaerothionin, caissarine B (76), recently isolated from the Brazilian sponge Aplysina caissara, is the only bromotyrosine-derived alkaloid bearing a 1,7-diamino-3-hydroxyheptane chain, a diamine moiety that has no precedent among natural products (66).…”
Section: B Spirocyclohexadienylisoxazoline Bromotyrosine Derivativesmentioning
confidence: 99%
“…Structurally related to aerothionin and homoaerothionin, caissarine B (76), recently isolated from the Brazilian sponge Aplysina caissara, is the only bromotyrosine-derived alkaloid bearing a 1,7-diamino-3-hydroxyheptane chain, a diamine moiety that has no precedent among natural products (66).…”
Section: B Spirocyclohexadienylisoxazoline Bromotyrosine Derivativesmentioning
confidence: 99%
“…In the case of the order Verongida, many of the species produce compounds with antimicrobial, antibacterial, cytotoxic and antitumor activity. 23,24 Nuclear enzymes that control and modify the topological states of DNA are known as topoisomerases. In mammalian cells, they are classified into types I and II, according to their mechanisms and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Both caissarines were identified by analysis of spectroscopic data. 9 However, due to the lost of the samples of both 1 and 2, we have been unable to measure their specific rotation and to evaluate their biological activities. Therefore, we have been interested to re-isolate the compounds in order to complete their characterization and to evaluate their biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, a first recollection of the sponge A. caissara did not provide any dibromotyrosine derivative. 9 Since the recollected sponge was stored in EtOH at room temperature for several weeks, we considered that the sponge metabolites could suffer degradation under these conditions. It has been indeed reported that dibromotyrosine metabolites of the sponge A. aerophoba can degrade in the presence of alcohol-H 2 O mixtures, since the enzymatic activity is not completely suppressed under such conditions.…”
Section: Introductionmentioning
confidence: 99%